Book Review: M. Beuthe, V. Himanen, A. Reggiani and L. Zamparine (eds.) Transport Developments and Innovations in an Evolving World - Geerlings, Harry (European Journal of Transport and Infrastructure Research, 2005)
Over the last few decades there has been a growing attention for the role of innovation in society.. Innovation plays an important role in the transport sector as well: the transportation sector manifests itself as a sector of continuous technological innovation. We even observe a certain fascination when it comes to the role of technology. And it is indisputable that technology has contributed to a more efficient use of energy, materials and capital. As a result, the demand of transport has increased rapidly over the last few decades, as is reflected in an increased car ownership and the increased number of passenger and freight kms. But it is also clear that this development goes hand in hand with substantial negative side effects (such as emissions and congestion).